Natural stereoisomeric flavonoids exhibit different disruptive effects and the mechanism of action on Aβ42 protofibril. Issue 35 (31st March 2021) - Zhan, Chendi; Lao, Zenghui; Tang, Yiming; Qiao, Qin; Wei, Guanghong
Abstract : Stereoisomers (+)-C and (−)-C show a better disruptive effect on Aβ42 protofibril than EC due to the steric effect caused by the conformational differences. Abstract : Our simulations reveal that two enantiomeric catechins display a better disruptive effect on Aβ42 protofibril than their stereoisomer epicatechin. Unexpectedly, we find that catechins adopt both collapsed and extended states, while epicatechin populates only an extended state. Their different protofibril-disruptive effects are mostly attributed to the steric effect caused by the conformational differences.